DEVELOPMENT OF A FAIR WAGE SYSTEM TO IMPROVE WORKERS' WALFARE FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Anto Apriyanto; Fadli Muhamad, Lili (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2024)
Islam views the issue of wages as having a lot to do with moral concepts, while the West does not. Even wages in Islam are not only limited to material (material or worldly) but to penetrate the boundaries of life, namely the dimension of the hereafter called merit, while the West does not. The implementation of the Western version of the wage system, which is currently still ongoing, is at least the background for the occurrence of unequal social and welfare disparities. The polemic of workers' wages has always been an endless discussion. Even though there is still something worse than the wages of workers, namely the wages of teachers and lecturers of small private foundations. Moreover, the school and campus are Islamic foundations. This paper is expected to provide a view on how the wage system should be implemented in accordance with the postulates of the Qur'an and Sunnah. This study uses a qualitative approach with secondary data. Then it was analyzed using content analysis. The results of the study show that the concept of wages in the Islamic view is the reward that a person receives for his work in the form of rewards in the world in a fair and polite manner and in the form of rewards in the hereafter because work has a dimension of worship. The principle must be based on voluntary agreement without coercion from both parties. A wage contract is valid with the existence of rights and obligations between the two, clearly stating the wage level, contract period, type, and nature of the work. The determination of wages in Islam must also be determined by the interaction of market forces on the supply and demand of labor, taking into account the aspects of justice and respect. In addition, the government also needs to set a minimum wage price if the market mechanism is unable to realize fair and decent wages for workers. It is also recommended that the minimum wage in Islam is determined based on the nishab zakat. Keywords: Wage, Salary, Labour, Teachers and Lecturers, Welfare.